2020
DOI: 10.1155/2020/3056067
|View full text |Cite
|
Sign up to set email alerts
|

Male Breast Cancer in Togo: Imaging and Clinicopathological Findings

Abstract: Background. Breast cancer in men is a rare condition, often diagnosed late. The purpose of this study was to describe its epidemiological, histopathological, and radiographic aspects in Togo. Materials and Methods. This was a descriptive retrospective study on cases of breast cancer in humans diagnosed histologically at the Laboratory of Anatomy Pathological and Imagery of the University Hospital in Lomé, over a period of 25 years (1995 to 2019). The parameters studied were epidemiological, anatomopathological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Luminal molecular subtype B (51.6%) was the most frequent subtype in our study, corroborating with the results found in the literature. 31 , 32 The proportion of triple-negative in our series is similar to the series in Saharan Africa, varying from 13.3% to 38%. 33 , 34 The mastectomy with lymph node dissection is most often performed because most tumors are diagnosed at a stage with lymph node invasion.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Luminal molecular subtype B (51.6%) was the most frequent subtype in our study, corroborating with the results found in the literature. 31 , 32 The proportion of triple-negative in our series is similar to the series in Saharan Africa, varying from 13.3% to 38%. 33 , 34 The mastectomy with lymph node dissection is most often performed because most tumors are diagnosed at a stage with lymph node invasion.…”
Section: Discussionsupporting
confidence: 75%
“…The molecular stratification of breast cancer has prognostic and therapeutic implications. [28][29][30][31] Patients with luminal A submolecular type cancer have a better prognosis and benefit from hormone therapy; those with luminal B submolecular type cancer have a better prognosis for chemotherapy. 36 Triple-negative molecular subtype cancers have a very poor prognosis according to the literature and are most often diagnosed in young women.…”
Section: Discussionmentioning
confidence: 99%
“…Mammography has long been regarded as the gold standard for breast cancer screening in high-income countries, and has led to significant reductions in mortality rates among women aged 50 and over who have participated in organized breast cancer programs mammography screening [20]. Mammographic screening proves to be beneficial when it is car- Socioeconomic dependence and late diagnosis reflect higher rates of breast cancer morbidity and mortality in developing countries [23]. The impact of mammography screening may be more beneficial in developing countries than what has been observed in developed countries [24].…”
Section: Discussionmentioning
confidence: 99%
“…BC commonly starts and accumulates in different parts of the breast including the ducts and lobules that will eventually metastasized to other parts of the body (CDC, 2021.). In male, breast cancer is a rare condition (Darre et al, 2020) that accounts for less than 1% of all cancers in men breast (Giordano et al, 2018) and less than 1% of all diagnosed cancers (Perkins, 2003). However, an escalation of number of breast cancer-diagnosed men have been reported, although at a lower rate (De Carmen et al, 2021).…”
Section: Discussionmentioning
confidence: 99%